2018
DOI: 10.1007/s00190-018-1130-6
|View full text |Cite
|
Sign up to set email alerts
|

Consistent realization of Celestial and Terrestrial Reference Frames

Abstract: The Celestial Reference System (CRS) is currently realized only by Very Long Baseline Interferometry (VLBI) because it is the space geodetic technique that enables observations in that frame. In contrast, the Terrestrial Reference System (TRS) is realized by means of the combination of four space geodetic techniques: Global Navigation Satellite System (GNSS), VLBI, Satellite Laser Ranging (SLR), and Doppler Orbitography and Radiopositioning Integrated by Satellite. The Earth orientation parameters (EOP) are th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The IAG Resolution 2 at the International Union of Geodesy and Geophysics (IUGG) General Assembly in Melbourne (2011) recommends that the highest consistency between the ICRF, the ITRF and the EOP should be a primary goal in all future realizations of the ICRS (IUGG Website 2022). Although the IUGG recommendation has not yet been fulfilled, research in this direction has been initiated and simultaneous estimation of CRF, TRF, and EOP have been achieved (Seitz et al 2014;Kwak et al 2018). At the international level, this topic is being addressed by the ICRF3 Working Group of the International Astronomical Union and by Sub-Commission 1.4 on the Interaction of Celestial and Terrestrial Reference Frames of the IAG.…”
Section: Unification Of Reference Frames and Earth Rotationmentioning
confidence: 99%
“…The IAG Resolution 2 at the International Union of Geodesy and Geophysics (IUGG) General Assembly in Melbourne (2011) recommends that the highest consistency between the ICRF, the ITRF and the EOP should be a primary goal in all future realizations of the ICRS (IUGG Website 2022). Although the IUGG recommendation has not yet been fulfilled, research in this direction has been initiated and simultaneous estimation of CRF, TRF, and EOP have been achieved (Seitz et al 2014;Kwak et al 2018). At the international level, this topic is being addressed by the ICRF3 Working Group of the International Astronomical Union and by Sub-Commission 1.4 on the Interaction of Celestial and Terrestrial Reference Frames of the IAG.…”
Section: Unification Of Reference Frames and Earth Rotationmentioning
confidence: 99%
“…The SLR and VLBI NEQs are free from datum constraints and thus only contain the datum information to which the respective observations are sensitive. The SLR and VLBI data processing was carried out with the Orbit Computation (-OC) and Radio Interferometry (-RI) branches of the DGFI Orbit and Geodetic parameter estimation Software (DOGS; Bloßfeld, 2015;Gerstl, 1997;Kwak et al, 2017), respectively. The resulting weekly (SLR) or session-wise (VLBI) NEQs for combination are provided in the SINEX v2.02 format.…”
Section: Satellite Laser Ranging and Very Long Baseline Interferometrymentioning
confidence: 99%
“…To compensate for the insufficient density of VLBI observations and the unstable GPS solutions, GPS observations from 17 globally distributed and relatively stable IGS sites were processed by GAMIT, and the VLBI observations from the same period were processed by OCCAM (Wei et al 2016). GNSS and VLBI observations from 2005 to 2015 were used to simultaneously estimate the EOP from an intertechnique combined normal equation (NEQ), the results indicated that the standard deviations of the EOP improved by the inter-technique combination, which demonstrates the benefits of a common estimation of all parameters (Kwak et al 2018). The VLBI observations from October 1 to 15, 2020 were estimated and compared with the ERP obtained from the simultaneous GPS data solved by GAMIT, the experimental results revealed that the accuracy of both solutions is in the same order of magnitude (Qian et al 2021).…”
Section: Introductionmentioning
confidence: 99%